El éxito de trabajar en conjunto: prácticas colaborativas recomendadas al diseñar un contrato de construcción - Otárola Azabache, Silvia (2023)
The construction industry is highly conflictive and adversarial. Given the existence of clauses that generate an evident imbalance between the parties and where the solutions proposed to result in the benefit of only one party, the need to incorporate collaborative practices that promote active and reciprocal cooperation between the parties during all stages of the project becomes more evident. This article aims to recommend three practices that, if included in the construction contract, help to carry out an efficient contract administration, to reduce the potential for possible conflicts, and, with it, to prioritize the project’s objectives.